APPLICATION OF C4.5 ALGORITHM FOR DETERMINATION OF THE COMMUNITY OF RECIPIENTS OF PROSPEROUS FAMILY CARDS IN THE VILLAGE OF SUKARAMAI BASED ON WEB - Intan Agustina; Juna Eska; Indra Ramadona Harahap (Informatika, Universitas Jenderal Soedirman, 2022)
The Prosperous Family Card (KKS) is a card given by the Government in lieu of a Social Protection Card (KPS). This card is a marker of underprivileged communities, people who have KKS will get Rice Assistance and Non-Cash Food Assistance (BPNT) every month. To receive the Prosperous Family Card (KKS), the government has set several criteria. As for how to solve the criteria that have been set, namely by utilizing data mining techniques. Data mining can also be interpreted as the process of extracting and extracting knowledge in a set of data using the C4.5 Algorithm. The C4.5 algorithm is a method that can be used for decision making that forms into a decision tree that can later be used as a basis for consideration in determining the community of recipients of the Prosperous Family Card (KKS). The purpose of this study is that the C4.5 algorithm can predict the community of recipients of prosperous family cards so that they can be used in determining the community of recipients of prosperous family cards (KKS) in Sukaramai village.